"I'm still dad": The Impact of Scleroderma on being a Father. Issue 1 (2nd January 2018) - Poole, Janet L.; Haygood, Donna; Mendelson, Cindy
ABSTRACT: The purpose of this study was to describe the experiences of fathers with scleroderma. Ten fathers with scleroderma were interviewed by telephone. Interviews were tape-recorded and transcribed verbatim. Two key themes emerged related to the emotional impact of the illness and the day to day realities of the illness with the unpredictability and rareness of the illness leading to ongoing feelings of isolation and fear of mortality. The negative influences of being a father with scleroderma included the inability of the fathers to participate in physical activities with their children such as outdoor sports and throwing balls. Being able to spend quality time with the child was a positive influence of the illness.